Analysis of Factors Affecting the Increase in the Number of Sesarea Sections at the H. Sahudin Kutacane Regional Hospital, Southeast Aceh - Mutiara Hikmah; Asriwati Asriwati; Aida Fitria; Lucia Lastiur (Journal La Medihealtico, 2020)
Caesarean section delivery is a method of delivery in which an incision or incision is made in the abdominal wall and uterine wall to remove the product of conception. This study aims to analyze the factors that influence the increase in the number of Sesarea sections in the H. Sahudin Kutacane Regional Hospital, Southeast Aceh, Aceh Province, Indonesia. This research method is a mixed method with a cross-sectional or explanatory sequential approach. The number of samples used for the quantitative study were 40 women giving birth by cesarean section, and for qualitative research using 4 informants consisting of 2 maternal, 1 obstetrician, and 1 clinic midwife. Data collection techniques in this study used primary, secondary, and tertiary data. The data analysis techniques used in this study were univariate, bivariate, and multivariate. The results of this study indicate that the factors of age (p = 0.221), education (p = 0.000), work (p = 0.733), parity (p = 0.000), medical indications (p = 0.140), JKN KIS (p = 0.000), knowledge (p = 0.007), and attitude (p = 0.000). Of the 5 related variables, there were no variables that directly affected the increase in cesarean section (p value => 0.05). There is a significant relationship between education, parity, national health insurance, knowledge and attitudes towards increasing cesarean section delivery in RSUD. H. Sahudin Kutacane, but of the five variables, none of the variables had an effect on the increase in the cesarean section rate in RSUD.H. Sahudin Kutacane.